Assessment of the risk factors associated with coliform mastitis among the pastoral herds: towards improving the quantity and quality of cow milk production in Nigeria - Makolo, Daniel; Suleiman, A.B. (Academia Journal of Biology, 2025)
Mastitis is a highly significant disease in dairy cattle, with significant economic implications such as decreased milk production, increased treatment, labour, and veterinary costs. While various contagious and environmental pathogens can cause mastitis, coliform bacteria are the most common cause of fatal mastitis in all types of production systems. Unlike many of the common contagious mastitis pathogens, Escherichia coli, genus Klebsiella and Enterobacter are opportunistic bacteria found in faeces and are present in even the most well-managed dairy environments. These coliforms can invade and cause mastitis through various routes, including hematogenous or percutaneous routes, but the most common route is through the teat canal. Therefore, it is necessary and meaningful to conduct a study to assess the risk factors associated with coliform-caused mastitis among pastoral herds in Nigeria. In this study, 147 lactating cows from 30 pastoral herds were investigated. California Mastitis Test Reagent was used for the detection of subclinical mastitis from the milk samples, while physical inspection and palpation of the udder were used for the detection of clinical mastitis among the studied cows from the pastoral herds. Structured questionnaires were used to assess the risk factors predisposing the pastoral herds to coliform-caused mastitis. The results obtained revealed that 29 (19.7%) of cows investigated were positive for subclinical mastitis and 13 (8.8%) of the mastitis-positive milk samples harboured coliform bacteria (E. coli and Klebsiella pneumoniae). The results of the risk factors analysis revealed a significant relationship (P = 0.00) between poor hygienic methods of rearing, milking cows and improper manure management, and mastitis caused by coliform bacteria among the pastoral herds. Therefore, improved hygienic methods of rearing, milking and proper manure management of the cows will drastically reduce the increasing prevalence of mastitis caused by coliforms among the pastoral herds in Nigeria.